A dialogia estética em Vincent van Gogh - Carvalho, Sônia de Fátima Elias Mariano (2009)
This dissertation aims at investigating, under French Discourse Analysis theoretical framework, images in its disposition at a symbolic aesthetical discursive space. Three of van Gogh s pieces have been taken as corpus: Sower, The (1888), Heat field with reaper and sun (1889) and Wheat field with crows (1890). van Gogh will be taken as aesthetics enunciative subject instancy for his alterity in plastic aesthetics space. Thus, such instancy is inscribed, discursively, in an interdiscourse, intercrossed by a discursive memory and historical conditions. There is a color interpellation from which a dialogy means, producing a variety of senses. However, image will be analysed in two procedures: a macro one in which interdiscourse will be emphasized and a micro one in which indiciary paradigm variables (traces and signals) (GINZBURG, 1993) will be considered as clues for examining aesthetics enunciative subject instancy s style. It was developed a methodological tool called indiciary paradigm table which evaluates the discursive potentialization on pictorial materiality. Three stages of analysis will be followed: a descritptive one, an interpretative one and a relational one. In the first, production conditions of plastic pieces will be scanned. In the second, regularities will be evidenced in a condensed matrix. Finally, in the third, symbolic clues will be put in conjunction in order to relate aesthetic singularities. Some theoretical extensions have been constructed in order to make analysis more precise such as: the extension of the concept of polyphony into polychromy and polyaestheticy. Pieces have been analyzed, considering color dialogism and enunciative trace meanings. Such meanings have been taken as visual operators in order to express sense production by a dialogism on colors, traces and symbolic meanings, taken as visual discursivity.